Risk factors for the development of invasive cancer in unresected ductal carcinoma in situ. Issue 4 (April 2018) - ,; Thompson, Alastair; Clements, Karen; Dobson, Hilary; Dodwell, David; Evans, Andrew; Hanby, Andrew; Hilton, Bridget; Kearins, Olive; Lawrence, Gill; Maxwell, Anthony; Pinder, Sarah; et al.
Abstract: Background: The natural history of ductal carcinoma in situ (DCIS) remains uncertain. The risk factors for the development of invasive cancer in unresected DCIS are unclear. Methods: Women diagnosed with DCIS on needle biopsy after 1997 who did not undergo surgical resection for ≥1 year after diagnosis were identified by breast centres and the cancer registry and outcomes were reviewed. Results: Eighty-nine women with DCIS diagnosed 1998–2010 were identified. The median age at diagnosis was 75 (range 44–94) years with median follow-up (diagnosis to death, invasive disease or last review) of 59 (12–180) months. Twenty-nine women (33%) developed invasive breast cancer after a median interval of 45 (12–144) months. 14/29 (48%) with high grade, 10/31 (32%) with intermediate grade and 3/17 (18%) with low grade DCIS developed invasive cancer after median intervals of 38, 60 and 51 months. The cumulative incidence of invasion was significantly higher in high grade DCIS than other grades ( p = .0016, log-rank test). Invasion was more frequent in lesions with calcification as the predominant feature (23/50 v. 5/25; p = .042) and in younger women ( p = .0002). Endocrine therapy was associated with a lower rate of invasive breast cancer ( p = .048). Conclusions: High cytonuclear grade, mammographic microcalcification, young age and lack of endocrine therapy were risk factors for DCIS progression to invasive cancer. Surgical excision of high grade DCIS remains the treatment of choice. Given the uncertain long-term natural history of non-high grade DCIS, the option of active surveillance of women with this condition should be offered within a clinical trial.